Nanoscale Transmitters Employing Cooperative Transmembrane Transport Proteins for Molecular Communication - tom Dieck, Teena; Brand, Lukas; Lotter, Sebastian; Castiglione, Kathrin; Schober, Robert; Schäfer, Maximilian (NANOCOM '24: Proceedings of the 11th Annual ACM International Conference on Nanoscale Computing and Communication, 2024)
This paper introduces a novel optically controllable molecular communication (MC) transmitter (TX) design, which is based on a vesicular nanodevice (ND) functionalized for the release of signaling molecules via transmembrane proteins. Due to its optical-to-chemical conversion capability, the ND can be used as an externally controllable TX for several MC applications such as bit transmission and targeted drug delivery. The proposed TX design comprises two cooperating modules, an energizing module and a release module, and depending on the specific choices for the modules allows for the release of different types of signaling molecules. After setting up a general system model for the proposed TX design, we conduct a detailed mathematical analysis of a specific realization. In particular, we derive an exact analytical and an approximate closed-form solution for the concentration of the released signaling molecules and validate our results by comparison with a numerical solution. Moreover, we consider the impact of a buffering medium, which is typically present in experimental and application environments, in both our analytical and numerical analyses to evaluate the feasibility of our proposed TX design for practical chemical implementation. The proposed analytical and closed-form models facilitate system parameter optimization, which can accelerate the experimental development cycle of the proposed ND architecture in the futur